I love my job because I can provide wheelchairs for persons with disabilities: English Communication Empowerment for a Disability Rights Organisation - Subekti, Adaninggar Septi; Susyetina, Arida; Ermerawati, Anesti Budi; Winardi, Andreas; Endarto, Ignatius Tri; Kurniawati, Lemmuela Alvita; Wati, Mega (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This community service programme was conducted in the form of an English communication empowerment programme for employees of OHANA, a disability rights organisation based in Yogyakarta. The programme consisted of ten 90-minute meetings conducted from early October 2022 up to mid-November 2022. The materials of this training included self-introduction, introducing others, making small talks with a wide range of topics, as well as job descriptions and job responsibilities. The programme was conducted in response to the need for OHANA employees to make more effective communications with foreign partners concerning their jobs as advocates of the rights of women and persons with disability. Despite the low attendance rate in some of the meetings due to the tight schedules of the OHANA employees in providing services to the community, the language empowerment programme can be considered successful seen from the engagement of the attending participants and the generally positive feedback from them. Several conclusions and recommendations are stated considering the degree of success of this programme for the betterment of future similar programmes.